Force Majeure in Islamic Law of Transaction: A Comparative Study of the Civil Codes of Islamic Countries - Mhd. Syahnan (Universitas Darussalam Gontor, 2013)
This paper attempts to shed lights on the performance of the obligations to a valid contract that can be frustrated by events beyond human control. Such events may have considerable impact on various designated legal principles and rules which is widely known as force majeure. The doctrine of unforeseen circumstances in contemporary legislation, on the main, is expressed in the same term which understandably as result of the origin derivation of the French law le theorie de l’imprévision. Although it is true that there is no such general principle of force majeure in classical Islamic law, the author argues that significant efforts have been made in synthesizing both the Islamic and Western law concepts. Accordingly, despite the fact that the traditional Islamic legal system has its own mechanism to deal with such events at the time of contract, to a certain extent, it has influenced its contemporary form of the concept of intervening conti- ngencies (nazariyyat al-jawa’ih ) as reflected in the Civil Codes of the Arab states. In addition, in response to the exigencies of the ever-increasing problems of modern life which brings with it alien concept, force majeure does not contradict with the provisions of the Shari‘ah since the views of Islamic jurisprudents (fuqahâ) can justifiably be referred to.